2017
DOI: 10.3390/min7020027
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometallurgical Process and Kinetics of Leaching Manganese from Semi-Oxidized Manganese Ores with Sucrose

Abstract: Abstract:The extraction of manganese from a semi-oxidized manganese ore was investigated with sucrose as the reducing agent in dilute sulfuric acid medium. The kinetics of leaching manganese from the complex ore containing MnCO 3 and MnO 2 was also investigated. The effects of sucrose and sulfuric acid concentrations, leaching temperature and reaction time on the total Mn (TMn), MnO 2 and MnCO 3 leaching were investigated. Results showed that MnCO 3 could more easily react with hydrogen ions than MnO 2 in ores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The fact that antimony leaching efficiency increased with increasing temperature and leaching time and remained the same with increasing L/S ratio suggests that the leaching rate is most likely limited by the chemical reactions at the solid−liquid interface rather than the diffusion of the reactants and products. 38 However, a more detailed kinetic study would be required to confirm if the leaching reactions are reaction-controlled, diffusion-controlled or a combination of both. The difficulty of increasing the antimony leaching efficiency above 80% could be due to the stability of some antimony mineral phases, which are not dissolved by the lixiviant (see later results).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that antimony leaching efficiency increased with increasing temperature and leaching time and remained the same with increasing L/S ratio suggests that the leaching rate is most likely limited by the chemical reactions at the solid−liquid interface rather than the diffusion of the reactants and products. 38 However, a more detailed kinetic study would be required to confirm if the leaching reactions are reaction-controlled, diffusion-controlled or a combination of both. The difficulty of increasing the antimony leaching efficiency above 80% could be due to the stability of some antimony mineral phases, which are not dissolved by the lixiviant (see later results).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When the leaching time was further increased, the leaching efficiency of antimony increased at much slower rate, with 88% leaching yield after 96 h. The leaching time did not have any effect on the leaching efficiency of lead. The fact that antimony leaching efficiency increased with increasing temperature and leaching time and remained the same with increasing L / S ratio suggests that the leaching rate is most likely limited by the chemical reactions at the solid–liquid interface rather than the diffusion of the reactants and products . However, a more detailed kinetic study would be required to confirm if the leaching reactions are reaction-controlled, diffusion-controlled or a combination of both.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of sulphuric acid varied from 2.5% to 15% (v/v) (0.46 M‐2.76 M), while the other parameters were maintained as follows: P.D. 10% (wt/v), 2[Critical Micelle Concentration] (CMC) surfactants (v/v), temperature 80 °C, reaction time 4 h. On increasing the acid concentration from 2.5% to 15% (v/v) (0.46 M‐2.76 M), the leaching efficiency of Fe, Co, Ni, and Cu increased exponentially, except for Mn 28,29 . This is consistent with the results obtained by Saldaña et al ., where the authors studied six operational variables by developing an analytical model for an acid‐reducing process of manganese nodules, and they concluded that the concentration of sulfuric acid in the system is not very relevant for the dissolution of MnO 2.…”
Section: Resultsmentioning
confidence: 99%
“…A reducing agent convert the insoluble MnO2 to soluble MnO. Manganese oxide ore can be extracted either by reduction-roasting followed by leaching or directly by reductive acid leaching using various reducing agents (Wang et al, 2017, Hariprasad et al, 2007, Zhang et al, 2018b, Habashi, 1993) such as ferrous sulfate (Vu et al, 2005), cornstalk (Cheng et al, 2009), sulfur dioxide (Sun et al, 2013), hydrogen peroxide (Khan and Kurny, 2014), sodium sulfide (Sheng and QIU, 2014), carbohydrates (Wu et al, 2014), waste tea (Qing et al, 2014), ethylenediaminetetraacetic acid (EDTA) (Zhang et al, 2018a, Zhang et al, 2018b, glucose (Pagnanelli et al, 2004), sawdust (Hariprasad et al, 2007) and oxalic acid (Sahoo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%